Homossexualidade em discurso: materializações discursivas da homofobia no facebook - Silva, Daniel Thiago Freire da (2018)
The present research represents a way to perceive how people inserted in the social network Facebook produce their discourses about the thematic one of the homosexuality. Methodologically, a temporal period was defined for insertion in this virtual environment which, together with selection filters, enabled the collection of the necessary data and, consequently, the construction of a textual file. Next, the analysis of what was collected was based on the theoretical-methodological assumption of the Discourse Analysis of the french line, which presents itself as a support for the study and understanding of the historical, social and ideological vestiges left behind in the words produced by people. In this context, the emergence of cyberspace and, more recently, of social networks, and especially Facebook, enabled individuals to transpose to these spaces their opinions and manifestations, encouraged by a supposed unlimited freedom of expression. Historically, homosexuality, despite being a legitimate manifestation of human diversity, as well as heterosexuality, bisexuality and all other forms of expression of humanity's affective and sexual desire, has been marginalized and socially repressed. To homosexuality was and still is fit the absolute silence, the non-speech, what should not jump in the eyes of the collective, the daring, what should be combated and expelled from normal coexistence. Homophobia, a complex and timeless phenomenon, manifests itself daily and systematically through physical and symbolic aggressions that hinder rights and opportunities, and attribute to the LGBTI population (lesbian, gay, bisexual, transgender and intersexual) a place of inferiority, disease, crime, of heresy. As it happens in life outside the network, the results verified by this research pointed out that this social network can represent a tool for propagating prejudice and discrimination with those who deviate from the established standard.